Maryam a.s/Mary and The Alienation of the Female Body: An Existentialist Feminist Analysis of Pregnancy in Sacred Narratives - Utami, Selvina Adistia; Fajriyah, Iklilah Muzayyanah Dini (the Faculty of Ushuluddin, UIN Sunan Gunung Djati Bandung, 2025)
This article investigates how the female voice and body are constructed in the annunciation and pregnancy narratives of Maryam in the Qur’an (QS Maryam: 19–20) and Mary in the Gospel of Luke (1:34). The research aims to examine how these sacred texts reflect women’s experiences of alienation and agency in relation to pregnancy, situated within the tension between divine will, patriarchal norms, and autonomy. Methodologically, the study employs a qualitative literature-based approach combined with feminist critical discourse analysis, grounded in Simone de Beauvoir’s existentialist feminism and supported by gender-sensitive hermeneutics. Classical tafsir and biblical commentaries are re-read alongside contemporary feminist theological and philosophical literature to trace how religious authority and cultural expectations shape the meaning of pregnancy. The analysis demonstrates that the narratives of Maryam/Mary encode a recurrent pattern of alienation of the female body: pregnancy appears as something that “happens” to women, their honour is tied to sexual purity, and their consent is articulated within heavily gendered structures. At the same time, the figures of Maryam and Mary retain elements of questioning, resistance, and spiritual strength that disrupt purely passive portrayals. The main contribution of this study lies in proposing an alternative reading of Maryam/Mary as symbols of transcendent, spiritual resistance rather than merely immanent reproductive roles. By highlighting alienation, bounded agency, and embodied subjectivity, the article expands feminist theological discourse. It offers a critical framework for rethinking motherhood, consent, and women’s bodily autonomy in contemporary Muslim and Christian contexts.